Hermann Wendland’s Botanical Explorations in Central America (1856-1857): II. In the Sarapiquí region, Costa Rica - Dowe, John Leslie (2023)
This paper corresponds to the second part of the account entitled Travel notes of the court gardener Hermann Wendland,published in 1857 in the magazine Hamburger Garten- und Blumenzeitung, of which the first part was recently translatedfor the journal Comunicación.